Infection and Immunometabolism in the Central Nervous System: A Possible Mechanistic Link Between Metabolic Imbalance and Dementia - Shinjyo, Noriko; Kita, Kiyoshi (Frontiers in Cellular Neuroscience, 2021)
Metabolic syndromes are frequently associated with dementia, suggesting that the dysregulation of energy metabolism can increase the risk of neurodegeneration and cognitive impairment. In addition, growing evidence suggests the link between infection brain disorders, including Alzheimer’s disease. The immune system and energy metabolism are in an intricate relationship. Infection triggers immune responses, which are accompanied by imbalance in cellular and organismal energy metabolism, while metabolic disorders can lead to immune dysregulation and higher infection susceptibility. In the brain, the activities of brain-resident immune cells, including microglia, are associated with their metabolic signatures, which may be affected by CNS infection. Conversely, metabolic dysregulation can compromise innate immunity in the brain, leading to enhanced CNS infection susceptibility. Thus, infection and metabolic imbalance can be intertwined to each other in the etiology of brain disorders, including dementia. Insulin and leptin play pivotal roles in the regulation of immunometabolism in the CNS and periphery, and dysfunction of these signaling pathways are associated with cognitive impairment. Meanwhile, infectious complications are often comorbid with diabetes and obesity, which are characterized by insulin resistance and leptin signaling deficiency. Examples include HIV infection and periodontal disease caused by an oral pathogen Porphyromonas gingivalis. This review explores potential interaction between infectious agents and insulin and leptin signaling pathways, and discuss possible mechanisms underlying the relationship between infection, metabolic dysregulation, and brain disorders, particularly focusing on the roles of insulin and leptin.